PENGARUH DIMENSI BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION EKSPATRIAT PADA HOTEL BINTANG LIMA DI NUSA DUA - BALI - Anna, Smirnova A; Dewi, I.G.A. Manuati; Putra, Made Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
Although the presence of expatriates have a positive impact for Bali tourism development, the high turnover of expatriates effect to the high costs incurred in the company. The purposes of this study is to test the Sablynski model which base on Schein’s Organizational Culture theory, which found organizational culture has negative influence on expatriate turnover intention. The study population was all expatriates in a five star hotel in Nusa Dua – Bali, which are 66 person. Data were analyzed using linear regression analysis with SPSS. The result proves that organizational culture negatively affect expatriates turnover intention. This study suggests the need to increase the sense of connection between expatriates and the company by improving the company's ability to identify the presence and duration of expatriates working in the company as well as the need for companies to make the standards of conduct and training on organizational culture.
Keywords: organizational culture, turnover intention, expats